The education of a coach - Halberstam, David (New York Hyperion, 2005)
Bill Belichick's 31 years in the NFL have been marked by amazing success--most recently, his Super Bowl wins with the New England Patriots have made him surpass Vince Lombardi. In this book, journalist Halberstam explores the nuances of both the game and the man behind it. Halberstam writes. "There was, I thought, a certain signature to a Belichick game... I was fascinated ... by the fact that he seemed so un-coachlike, or perhaps the prototype for a very different kind of modern coach in what is an increasingly complicated game. He wasn't in any way charismatic, and he made no attempt to be charismatic--if anything, quite the reverse, but he always seemed to be one step ahead of everyone else." Set apart by his Wesleyan education, Belichick approaches coaching differently than anyone else in the NFL. Here, we learn why and how.--From publisher description.
Keywords: Belichick, Bill; New England Patriots (Football team); Football coaches -- United States -- Biography